Språkpolicyer inom sjukvården. En studie av förpliktelsemodalitet i språkprogram för tvåspråkiga områden i Finland - Heinonen, Rebecka (Foreningen for nordisk filologi rf, 2026)
The aim of the study is to analyze how obligation is expressed in the language policies of four bilingual healthcare regions in Finland. These policies give guidelines for how the personnel and patients can communicate in accordance with the language rights granted to speakers of Swedish and Finnish in the Finnish legislation. Swedish speakers are usually a minority within the regions. The analyses are based on Systemic-Functional Grammar. Auxiliary verbs expressing obligation are analyzed both quantitatively and qualitatively, and incongruent expressions of obligation are discussed. The results show how expressions of obligation reflect the status of the languages in the organizations in question and attitudes towards bilingualism in the regions in general.